Studying the effects of human resource management practices and corporate social responsibility on employee performance in Kalinisan Workers Service Cooperative - Ladlad, Jose Manuel M. (Animo Repository, 2022)
Employee performance is an essential element in an organization's competitiveness. There exist various factors that affect the performance of the employees. This research paper mainly investigates the effects of human resource management practices and corporate social responsibility on employee performance in the Kalinisan Workers Service Cooperative. Different human resource management practices and corporate social responsibility activities are identified and critically studied to reveal their effects on employee performance. The researchers were able to gather quantitative data that consisted of one hundred thirty-two (132) respondents, while also interviewing nine (9) respondents as qualitative data in the said company. To test the hypothesis of the study, the researchers ensured that the 4 assumptions— Durbin-Watson Test, Collinearity Statistics, Normality Test, and Test for Homoscedastic were met. The resaerchers then proceeded to utilize Pearson’s Correlation Analysis, and Regression Analysis (Linear Regression) to test the hypothesis of the study. Based on the results of the Pearson correlation analysis conducted for the study, there exists a significant positive correlation between the Human Resource Management Practices subconstructs and Employee Performance. Likewise, there also exists a significant positive correlation between Corporate Social Responsibility and Employee Performance. Furthermore, based on the linear regression analysis conducted for studying the effects of Human Resource Management Practices and Corporate Social Responsibility towards Employee Performance that both the Human Resource Management Practices subconstructs and Corporate Social Responsibility have a significant positive effect on Employee Performance within Kalinisan Workers Service Cooperative. Subsequently, the study recommended Kalinisan Workers Service Cooperative to improve on their Human Resource Management Practices and Corporate Social Responsibility. The researchers suggest to update the expectations section of the job description and the usage of daily monitoring shifts to generate valuable feedback. Handpicking employees to be selected for the company is highly recommended. Furthermore, an increased presence of team leaders/supervisors as well as to provide more personalized work-related assistance whenever needed are deemed necessary for its workforce. The researchers recommend non-monetary compensations as well as milestone-based incentives. In addition, the frequency of training should be returned to being conducted quarterly, all the while integrating more the use of technology and feedback from employees. The researchers recommend the use of more job advertisement websites in recruiting employees. The company is also suggested to have seminars focused on raising awareness in support of equal opportunities for employees and against discrimination. Moreover, it is also recommended that the company should engage its employees more when it comes to counseling, planning assistance, and work-life balance policies. The researchers also recommend involving the employees in the planning and execution of community-based activities, as well as providing aid in the respective communities of the employees. Additionally, the practices related to the protection and preservation of the environment are sufficient and recommended to continuously implement the practices regarding the welfare of the environment.